Assessing Intergenerational Earnings Persistence among German Workers - Philipp Eisenhauer; Friedhelm Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In this study we assess the relationship between father and son earnings among (West) German Workers. To reduce the lifecycle and attenuation bias a novel sampling procedure is developed and applied to the German Socio-Economic Panel (SOEP) 1984-2006. Our preferred point estimate indicates an intergenerational earnings elasticity of 1/3 .
Keywords: J62; J32; J21; 330; Intergenerational Mobility; Lifecycle; Permanent Earnings; Wages